Hands-on RESTful web API design patterns and best practices design, develop, and deploy highly adaptable, scalable, and secure RESTful web APIs - Subramanian, Harihara; Raj, Pethuru (Packt Publishing, 2019)
REST architecture (style) is a pivot of distributed systems, simplify data integration amongst modern and legacy applications leverages through the RESTful paradigm. This book is fully loaded with many RESTful API patterns, samples, hands-on implementations and also discuss the capabilities of many REST API frameworks for Java, Scala, Python and Go.
Includes bibliographical references. - Online resource; title from title page (Safari, viewed March 22, 2019)
Keywords: Application program interfaces (Computer software); Web applications; Computer networks -- Management; Cloud computing; Interfaces de programmation d'applications; Applications Web; Réseaux d'ordinateurs; Gestion; Infonuagique; APIs (interfaces); Computer networks; Management